Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture: Report of the first project planning workshop, 6-10 February 2012, Rome, Italy - Vernooy, Ronnie; Bioversity International (2012)
This report summarizes the policy, research and capacity development activities that research teams from Bhutan, Burkina Faso, Costa Rica, Côte d’Ivoire, Guatemala, Nepal, Rwanda and Uganda and partner organizations will jointly carry out for the project “Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture”.